The Effect of Kahoot! to Enhance 11th graders student’s Reading Comprehension of Discussion Texts : Penelitian - Arangga Java Ramadona; Rahayu Kuswardani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aimed to investigate the effect of Kahoot! on enhancing 11th graders’ reading comprehension in discussion texts. The research used Kahoot! as an interactive teaching media to support students’ learning process in reading activities. This study employed a quantitative quasi-experimental design involving two classes of 11th grade students, with 24 students in each class. One class was assigned as the experimental group and the other as the control group. Both groups were given pre-test and post-test consisting of 20 questions. The experimental group was taught using Kahoot!, while the control group used conventional teaching media. The data were analyzed using the Mann–Whitney U test to determine the significance of the treatment. The result showed that there was no statistically significant difference between the control and experimental groups in students’ reading comprehension of discussion texts. However, the effect size result indicated a moderate effect, showing that Kahoot! still gave a meaningful practical contribution to students’ learning outcomes. In conclusion, Kahoot! can be used as an alternative teaching media to create a more interactive and engaging learning environment in teaching reading comprehension, particularly in discussion texts.